THE INFLUENCE OF TECHNOPRENEURSHIP ON HUMAN RESOURCES IN SMEs SECTOR - Tio, Lina; Yadewani, Dorris (JURNAL DIMENSI, 2025)
In the digital era, the role of human resources in driving the adoption of technology and innovation in the SME sector is becoming increasingly important. SMEs that contribute significantly to the Indonesian economy face challenges in adopting technology amidst global competition. This study examines the influence of technopreneurship on human resources in the SME sector using the Systematic Literature Review (SLR) method. Through SLR, this study aims to analyze scientific literature to understand how the application of technopreneurship affects human resources in SMEs. The results of the study indicate that technopreneurship supported by the quality of human resources is the main key to successful business development. This study also reveals the importance of human resources in managing organizational change, building a culture of innovation, and facilitating continuous learning as well as factors that motivate becoming a technopreneur.